Medico Social Profile Of Rural Pregnancies - Natu Maya; Shaikh Nasreen; Bhosale Nisha (Wolters Kluwer Medknow Publications, 1986)
Study shows social cultural and economic background of 500 riral pregnant mothers. Findings about pattern of intranatal care and puerperium are presented.